PHARMACOVIGILANCE STUDY IN GERIATRIC POPULATION - Nagaraju, Kiran; Manasa S; Manjunath R (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: Pharmacovigilance is defined as the science and activities concerned with the detection, assessment, understanding and prevention of adverse reactions to medicines. Main goal of pharmacovigilance in geriatric is to improve the safe and rational use of medicines and thereby improving patient care, health of the society. Pharmacovigilance is particularly concerned with the adverse drug reactions (ADR's). Hence, a closer pharmacovigilance studies are much needed in the older age group due to polypharmacy, which can cause ADR's leading to hospital readmission and the direct and indirect treatment cost to treat the ADR's. The objective of this study was to assess the prescribing practice and ADR's in geriatric patients with two or more comorbid condition during the stay in the hospital and to follow-up on 15th, 30th, 45th, 60th, 75th and 90th day after discharge. Methods: The study was conducted in Medicine Department, Kempegowda Institute of Medical Science Hospital and Research Centre, Bengaluru. It is a non-randomized observational prospective study conducted for a period of 6 months, to assess the prescribing pattern and incidence of ADR in the geriatric population. We made an attempt to assess the incidence of ADRs after discharge from the hospital by doing follow-ups. Results: Among the 50 patients included during the study, 29 (58%) patients were between the age group of 60 and 65 years, out of which 20 were female, and 9 were found to be male patients. Out of 50 patients, 40 (37.7%) patients suffered from hypertension, 30 (28.3%) patients had diabetes mellitus. The most commonly used antihypertensive drug was found that 20 (33.8%) patients were on calcium channel blockers which were used majorly, in anti-diabetic drugs, insulin was used in 19 (44.1%) patients, followed by 10 (23.2%) patients who were prescribed oral hypoglycemic like metformin. Number of drugs prescribed per prescription was found that 68% of patients were prescribed with 6-10 drugs. Among the study population, we found the incidence of three mild ADRs during follow-up. During analyzing of prescription, we found totally 122 drug interactions, out of which 83 (68%) were moderate, 30 (25%) were mild and 9 (7%) were found to be severe drug interactions. Conclusion: We observed that monitoring of drugs for ADRs in the geriatric population is mandatory due to their polypharmacy. Follow-up studies after discharge for monitoring of ADR will be one step ahead to improve the quality of life. This can reduce the hospital readmission, which can in turn reduce to the economic burden of the patients. Keywords: Pharmacovigilance, Adverse drug reactions, Geriatric, Polypharmacy. Â